Efforts to Realize National Standard School Administration at SMKS Bina Insani Malunda, Majene - Elviana, Elviana; Arhas, Sitti Hardiyanti; Isgunandar, Isgunandar (ASHA Publishing, 2025)
School administrative is a series of processes, policies, and practices that are implemented to manage school activities effectively and efficiently. The goal is to ensure that all administrative activities support the achievement of educational goals, in accordance with the established standards. The main purpose of this study is to find out the efforts to realize national standard school administrative governance and to find out the supporting and inhibiting factors in efforts to realize national standard school administrative governance at SMKS Bina Insani Malunda Majene Regency. This research is qualitative descriptive research. This research focuses on efforts to realize national standard school administrative governance based on planning, organizing, implementing, and supervising indicators. To achieve the research objectives, data collection techniques were used, namely observation, interviews, and documentation. Based on the results of the study, it shows that efforts to realize national standard school administrative governance at SMKS Bina Insani Malunda Majene Regency can be seen from the indicators of planning, organizing, implementing, and supervising in the